In-situ carbon-coated cobalt-doped lithium manganese iron phosphate and preparation method thereof

Through the preparation method of in-situ carbon coated with cobalt-doped lithium manganese iron phosphate, the problems of low cyclic stability and conductivity of lithium manganese iron phosphate are solved, and a high energy density and high safety lithium-ion battery positive electrode material is realized. Simplifies the process and reduces costs.

CN119263244AActive Publication Date: 2025-01-07RUYUAN DONGYANGGUANG NEW ENERGY MATERIAL CO LTD +1

Patent Information

Application Number
CN202411359306.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the prior art, lithium manganese iron phosphate has poor cycle stability and low conductivity, complex preparation process and high cost, making it difficult to achieve a lithium-ion battery positive electrode material with high energy density and high safety.

Method used

The preparation method of in-situ carbon coated cobalt-doped lithium manganese iron phosphate is adopted. The metal-organic frame precursor reacts with the lithium source and phosphorus source to form Co-doped lithium manganese iron phosphate, and the Co elements are evenly distributed in the crystal lattice. Catalyzing the formation of highly conductive carbon nanotubes by organic ligands, improving conductivity and compaction density.

Benefits of technology

It significantly improves the conductivity and compaction density of lithium manganese iron phosphate, improves the rate performance and cycle stability of lithium-ion batteries, simplifies the preparation process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263244A_ABST
    Figure CN119263244A_ABST
Patent Text Reader

Abstract

The invention discloses in-situ carbon-coated cobalt-doped lithium manganese iron phosphate and a preparation method thereof.The preparation method comprises the steps that a metal-organic framework precursor FexMn1-x-yCoy-MOF is prepared, x is larger than 0 and smaller than 1, y is larger than 0 and smaller than 0.01, then the metal-organic framework precursor is mixed with a lithium source and a phosphorus source, grinding treatment and spray drying are conducted, and the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate is obtained. And calcining in an inert atmosphere to obtain the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate. Uniform Co doping is formed in situ on a lithium manganese iron phosphate crystal lattice, the Co element can occupy the Fe site or Mn site in lithium manganese iron phosphate, the Co element can catalyze an organic ligand to form a high-conductivity carbon nanotube in situ in the sintering process, the high-conductivity carbon nanotube is interspersed on the surface of an in-situ carbon-coated lithium manganese iron phosphate particle, and the high-conductivity carbon nanotube and the in-situ carbon-coated lithium manganese iron phosphate particle have a synergistic effect; meanwhile, the conductivity, the stability and the compaction density of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery electrode materials, and more specifically, relates to an in-situ carbon-coated cobalt-doped lithium manganese iron phosphate and a preparation method thereof. Background Art

[0002] Due to its advantages of high safety and low cost, lithium iron phosphate has become the mainstream lithium-ion battery positive electrode material in today's new energy vehicles and large-scale energy storage fields. However, there is limited room for improvement in its performance such as capacity and energy density, and there is an urgent need to develop new high-energy-density lithium battery positive electrode materials. Compared with lithium iron phosphate, lithium iron manganese phosphate has a similar olivine structure, theoretical mass specific capacity, and excellent kinetic and thermodynamic stability. It forms a solid solution material of lithium manganese phosphate by doping manganese into lithium iron phosphate, which can effectively be compatible with the high safety and stability of lithium iron phosphate. At the same time, the introduction of manganese can increase the voltage platform of the material and thus increase the energy density of the phosphate material, making it a high-energy-density, high-safety lithium-ion battery positive electrode material. However, with the increase of the manganese doping ratio, Mn 3+ The Jahn-Teller effect and manganese dissolution caused by lithium manganese iron phosphate make the cycle stability poor. In addition, due to the low electronic and ionic conductivity of lithium manganese phosphate, the conductivity of lithium manganese iron phosphate still needs to be improved.

[0003] Metal-organic framework (MOF) is a three-dimensional framework of periodically arranged atoms. It is a porous coordination polymer formed by organic bridging molecules (i.e. ligands) and metal ions / metal clusters. Using metal-organic framework as a precursor to prepare lithium manganese iron phosphate positive electrode materials can make the metal elements evenly distributed. In addition, the organic ligands in the metal-organic framework can serve as an effective carbon source. During the sintering process, a carbon layer is formed on the surface of the material to wrap the surface of the material. On the one hand, it can improve the conductivity of the material and reduce direct contact with the electrolyte. On the other hand, it can inhibit the excessive growth and agglomeration of nanoparticles during the sintering process, and alleviate the volume expansion effect during the charge and discharge process.

[0004] The existing technology for preparing lithium manganese iron phosphate using metal-organic framework as precursor has the following bottlenecks for industrial application: 1) Ultra-low temperature freeze drying is required to prepare gel or ultrasound-assisted means, which has poor compatibility with lithium iron phosphate production line equipment, and the prepared lithium manganese iron phosphate has a low compaction density; 2) A secondary process is adopted in which lithium manganese iron phosphate is first synthesized and then modified with MOF to synthesize a composite lithium manganese iron phosphate material. The metal ions in MOF are easy to form metal elemental impurities, resulting in reduced electrochemical activity of the material; and the production process is complicated and the production cost is high. Summary of the invention

[0005] In order to solve the above-mentioned defects of the prior art, the primary purpose of the present invention is to provide a method for preparing in-situ carbon-coated cobalt-doped lithium manganese iron phosphate, thereby obtaining high-density lithium manganese iron phosphate and improving its conductivity.

[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing in-situ carbon-coated cobalt-doped lithium manganese iron phosphate comprises the following steps:

[0008] S1. In an inert atmosphere, dissolving an iron source, a manganese source and a cobalt source in a solvent to obtain a solution A;

[0009] S2. In an inert atmosphere, the organic ligand and the solvent are mixed uniformly to obtain a solution B;

[0010] S3. adding solution A to solution B and stirring evenly, reacting in an inert atmosphere to obtain a mixed slurry, followed by solid-liquid separation and washing to obtain a metal-organic framework precursor;

[0011] S4. The metal-organic framework precursor obtained in step S3 is mixed with a lithium source and a phosphorus source, subjected to grinding treatment, spray drying, and calcined under an inert atmosphere to obtain in-situ carbon-coated cobalt-doped lithium manganese iron phosphate;

[0012] The general formula of the metal-organic framework precursor is Fe x Mn 1-x-y Co y -MOF, wherein 0<x<1, 0<y<0.01.

[0013] The present invention first prepares Fe x Mn 1-x-y Co y -MOF (0<x<1, 0<y<0.01) precursor, and then mixing it with a lithium source and a phosphorus source to react, Co-doped lithium iron manganese phosphate can be formed in situ. The Co element can occupy the Fe site or Mn site in the lithium iron manganese phosphate and be evenly distributed in the lithium iron manganese phosphate lattice to form a solid solution phase similar to lithium iron manganese phosphate, which can effectively improve the conductivity of the material and inhibit manganese dissolution. Since Co can be calcined in an inert atmosphere to catalyze the in situ formation of highly conductive carbon nanotubes by organic ligands that are interspersed on the surface of the lithium iron manganese phosphate particles, the conductivity of the material is significantly improved. In addition, the dense carbon nanotube coating generated in situ can effectively optimize the stacking mode of the nanoparticles, thereby increasing the compaction density of the material, making it a high energy density positive electrode material.

[0014] Furthermore, the general formula of the metal-organic framework precursor is Fe x Mn 1-x-y Co y-MOF, wherein 0<x<1, 0.001<y<0.006.

[0015] Although the amount of Co doping in the metal-organic framework precursor is beneficial to improving the compaction density of the prepared in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composite material, the excessive Co doping in the metal-organic framework precursor makes it easy to form a composite composed of cobalt element, cobalt manganese iron phosphate solid solution phase or other phases such as cobalt phosphide during sintering, affecting the actual capacity, thereby reducing the electrochemical performance of the composite material. Therefore, the amount of Co doping in the metal-organic framework precursor selected in the present invention is within a certain range, which is beneficial to improve the compaction density of the lithium manganese iron phosphate composite material, while ensuring that the Co element forms a place-occupying doping in the lithium manganese iron phosphate, and improving the electrochemical performance of the positive electrode material.

[0016] Furthermore, in step S4, the molar ratio of the lithium source, the phosphorus source and the metal-organic framework precursor is Li:P:(Fe+Mn+Co)=0.95-1.15:0.95-1.15:1.

[0017] Furthermore, in step S4, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium silicate, lithium sulfate, lithium phosphate, lithium orthosilicate, lithium permanganate, lithium metaphosphate, lithium fluoride, lithium bromide, lithium oxide, lithium nitride, lithium sulfide, lithium oxalate, lithium formate, lithium octanoate, lithium citrate, lithium salicylate, lithium trifluoroacetate, lithium acetoacetate, lithium difluorophosphate, lithium hexafluorophosphate, lithium benzoate, lithium pyruvate, lithium acetate, lithium methoxide, and lithium ethoxide.

[0018] Furthermore, the phosphorus source in step S4 is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, lithium phosphate, sodium pyrophosphate, ammonium hypophosphite, ammonium polyphosphate, ammonium hexafluorophosphate, sodium phosphite, sodium metaphosphate, sodium tripolyphosphate, and sodium hexafluorophosphate.

[0019] Furthermore, the calcination treatment in step S4 is heating to 500-900° C. at a heating rate of 0.5-20° C. / min for heat preservation sintering.

[0020] Furthermore, the heat preservation sintering time is 5 to 20 hours.

[0021] In some embodiments of the present invention, in step S4, the heat preservation sintering is followed by air flow crushing and screening to obtain the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate.

[0022] Furthermore, the inert atmosphere in S4 is nitrogen and / or argon, and further, the oxygen content is controlled to be less than 10 ppm.

[0023] Furthermore, the grinding process in step S4 is wet ball milling, specifically, the metal-organic framework precursor, lithium source, phosphorus source, ethanol and ultrapure water obtained in step S3 are mixed to prepare a slurry, and the slurry is placed in a sand mill and ground using 0.2-0.3 mm zirconium balls to grind the slurry to a particle size of ≤0.2 μm. The volume ratio of ethanol to ultrapure water is 1:1; and the solid content of the slurry is 30-40%.

[0024] Furthermore, the spray drying in step S4 is specifically to feed the ground slurry into a spray drying system, and the control system sets the air inlet temperature to 200-260°C and the air outlet temperature to 100-130°C, and adjust the feed amount according to the particle size of the spray-dried material and the air outlet temperature to obtain a spray powder. 50 ≤25μm.

[0025] Furthermore, the reaction temperature in step S3 is 80-120°C.

[0026] Furthermore, the reaction time in step S3 is 5 to 30 hours, and more preferably 12 to 24 hours.

[0027] Furthermore, the solution used for washing in step S3 is a mixed solution of dimethyl diformamide and ultrapure water (V:V=1:1).

[0028] Furthermore, the ratio of the molar amount of the organic ligand added in step S2 to the total molar amount of the iron element in the iron source, the manganese element in the manganese source and the doped cations is 1:(0.5-10).

[0029] Furthermore, the solvent in step S2 is dimethylformamide and / or ultrapure water. Preferably, the solvent is a mixture of dimethylformamide and ultrapure water in a volume ratio of 1:1.

[0030] In some embodiments of the present invention, the step S2 is to stir and mix the organic ligand and the solvent at a temperature of 80 to 120° C. in an inert atmosphere to obtain a solution B.

[0031] Furthermore, the inert atmosphere in step S2 is nitrogen and / or argon.

[0032] The organic ligand used in the present invention can be any organic ligand known in the art that can be used to prepare a metal-organic framework.

[0033] Furthermore, the organic ligand in step S1 is at least one of benzoic acid, 1,2-phthalic acid, 1,3-phthalic acid, 1,4-phthalic acid, 1,2,4-benzenetricarboxylic acid, 1,3,5-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid, 2,5-dihydroxyterephthalic acid, 2,6-naphthalene dicarboxylic acid, fumaric acid, citric acid, oxalic acid, and 4,4'-biphenyl dicarboxylic acid.

[0034] Furthermore, the solvent in step S1 is dimethylformamide and / or ultrapure water. Preferably, the solvent is a mixture of dimethylformamide and ultrapure water in a volume ratio of 1:1.

[0035] The iron source, manganese source and cobalt source used in the present invention can be any one or more iron salts, manganese salts and cobalt salts known in the art for preparing positive electrode active materials.

[0036] Furthermore, the iron source in step S1 is one or more of ferric chloride, ferrous chloride, ferrous sulfate, ferric sulfate, ferric nitrate, ferric acetate, ammonium ferric sulfate, ferric citrate, and ferrous oxalate.

[0037] Furthermore, the manganese source in step S1 is one or more of manganese chloride, manganese sulfate, manganese nitrate, manganese carbonate, manganese acetate, and manganese oxalate.

[0038] Furthermore, the cobalt source in step S1 is one or more of cobalt dichloride, cobalt sulfate, cobalt acetate, and cobalt nitrate.

[0039] Furthermore, the inert atmosphere in step S1 is nitrogen and / or argon.

[0040] Another object of the present invention is to provide an in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared by the above preparation method.

[0041] Furthermore, the compaction density of the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate is ≥2.4 g / cm 3 , powder resistance <14Ω·cm.

[0042] Another object of the present invention is to provide a positive electrode sheet, which comprises the above-mentioned in-situ carbon-coated cobalt-doped lithium manganese iron phosphate.

[0043] Furthermore, the positive electrode sheet further includes a conductive current collector, a binder, a conductive agent, etc. In some embodiments of the present invention, the conductive current collector may be any conductive current collector for a positive electrode known in the art, such as aluminum foil or carbon-coated aluminum foil; the binder may be any binder known in the art, such as sodium hydroxycellulose, polyvinylidene fluoride, styrene-butadiene rubber or one or more thereof; the conductive agent may be any conductive agent known in the art, such as acetylene black, graphene, carbon nanotubes or one or more thereof.

[0044] Another object of the present invention is to provide a battery, comprising the above-mentioned positive electrode sheet.

[0045] Furthermore, the battery also includes a negative electrode sheet, a separator located between the positive electrode sheet and the negative electrode sheet, and an electrolyte.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The present invention prepares a metal-organic framework precursor Fe x Mn 1-x-y Co y -MOF, and then prepare in-situ carbon-coated cobalt-doped lithium manganese iron phosphate with lithium source and phosphorus source, which can achieve uniform distribution of iron, manganese and doped cobalt metal elements at the atomic level in lithium manganese iron phosphate. The Co element is evenly distributed in the lithium manganese iron phosphate lattice and forms a place-occupying doping, which is beneficial to inhibit the dissolution of manganese and effectively improve the conductivity of the material, thereby improving the electrochemical performance of lithium manganese iron phosphate as a positive electrode material; at the same time, Fe x Mn 1-x-y Co y -MOF is used as a carbon source template. After high-temperature sintering, a uniformly coated carbon layer can be generated in situ on the surface of the cobalt-doped lithium manganese iron phosphate material without the need for an external carbon source. This can not only effectively improve the conductivity of the material and alleviate the volume expansion effect during the charge and discharge process, but also effectively inhibit the agglomeration and excessive growth of cobalt-doped lithium manganese iron phosphate particles. In addition, calcination of Co in an inert atmosphere can catalyze the in situ generation of highly conductive carbon nanotubes by organic ligands that are interspersed on the surface of the material, thereby optimizing the stacking mode of the nanoparticles and significantly improving the conductivity and compaction density of the material. The preparation method of the present invention does not require a pre-sintering process or a secondary sintering process, and is a low-energy consumption, simplified process, kilogram-level / ton-level lithium manganese iron phosphate preparation technology route.

[0048] The in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared by the present invention is a nanoscale positive electrode material with high compaction density and low powder resistance and good structural stability. When applied to lithium-ion batteries, the conductivity, rate performance and cycle stability are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The first cycle charge and discharge curve of the carbon-coated cobalt-doped lithium manganese iron phosphate obtained in Example 1 of the present invention and Comparative Example 1 at a current density of 0.1C.

[0050] Figure 2 This is a scanning electron microscope characterization image of the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate according to Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.

[0052] Example 1

[0053] 1.Fe 0.4 Mn 0.598 Co 0.002 -Synthesis of MOF

[0054] First, under a nitrogen atmosphere, 1.495 mol of manganese chloride tetrahydrate, 1 mol of ferric chloride hexahydrate and 0.005 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0055] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 202.5 g of 1,4-phthalic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 700 rpm for 30 min at 110° C. to prepare the bottom liquid in the reactor.

[0056] Furthermore, the prepared iron, manganese and cobalt mixed salt solution A was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 110° C. for 20 hours to obtain a mixed slurry B.

[0057] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.4 Mn 0.598 Co 0.002 -MOF precursors.

[0058] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0059] Lithium carbonate is used as lithium source, ammonium dihydrogen phosphate is used as phosphorus source, Fe 0.4 Mn 0.598 Co 0.002 -MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.4 Mn 0.598 Co 0.002-MOF precursor was mixed with ethanol and ultrapure water (V:V=1:1) to prepare a slurry with a solid content of 35%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50 When the particle size is less than 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 240°C and an outlet temperature of 100°C. 50 ≤25μm) and the outlet air temperature to adjust the feed amount and obtain spray powder.

[0060] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content was less than 10 ppm), heated to 700° C. at a heating rate of 3° C. / min, and sintered at 700° C. for 10 h.

[0061] After the nitrogen atmosphere box furnace naturally cooled to room temperature, the sintered powder was air flow crushed and then sieved with a sieve to obtain in-situ carbon-coated cobalt-doped LiFe 0.4 Mn 0.598 Co 0.002 PO4 material.

[0062] Example 2

[0063] 1.Fe 0.5 Mn 0.496 Co 0.004 -Synthesis of MOF

[0064] First, under a nitrogen atmosphere, 1.24 mol of manganese chloride tetrahydrate, 1.25 mol of ferric chloride hexahydrate and 0.01 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0065] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 202.5 g of 1,4-phthalic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 600 rpm at 105° C. for 30 min to prepare the bottom liquid in the reactor.

[0066] Furthermore, the prepared iron, manganese and cobalt mixed salt solution A was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 105° C. for 24 hours to obtain a mixed slurry B.

[0067] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.5 Mn 0.496Co 0.004 -MOF precursors.

[0068] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0069] Lithium carbonate is used as lithium source, ammonium dihydrogen phosphate is used as phosphorus source, Fe 0.5 Mn 0.496 Co 0.004 -MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.5 Mn 0.5 -MOF precursor was mixed with ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 37%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50 When the particle size is less than 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 250°C and an outlet temperature of 105°C. 50 ≤25μm) and the outlet air temperature to adjust the feed amount and obtain spray powder.

[0070] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm), heated to 780° C. at a heating rate of 2° C. / min, and sintered at 780° C. for 9 h.

[0071] After the nitrogen atmosphere box furnace naturally cools to room temperature, the sintered powder is air flow crushed and then sieved with a sieve to obtain the in-situ carbon-coated cobalt-doped LiFe 0.5 Mn 0.496 Co 0.004 PO4 material.

[0072] Example 3

[0073] 1.Fe 0.3 Mn 0.696 Co 0.004 -Synthesis of MOF

[0074] First, under a nitrogen atmosphere, 1.74 mol of manganese chloride tetrahydrate, 0.75 mol of ferric chloride hexahydrate and 0.01 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0075] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 202.5 g of 1,4-phthalic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 700 rpm for 30 min at 114°C to prepare the bottom liquid in the reactor.

[0076] Furthermore, the prepared iron, manganese and cobalt mixed salt solution A was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 114° C. for 24 hours to obtain a mixed slurry B.

[0077] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.3 Mn 0.696 Co 0.004 -MOF precursors.

[0078] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0079] Lithium carbonate is used as lithium source, ammonium dihydrogen phosphate is used as phosphorus source, Fe 0.3 Mn 0.696 Co 0.004 -MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.3 Mn 0.696 Co 0.004 -MOF precursor was mixed with ethanol and ultrapure water (V:V=1:1) to prepare a slurry with a solid content of 32%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50 When the particle size is less than 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 230°C and an outlet temperature of 110°C. 50 ≤25μm) and the outlet air temperature to adjust the feed amount and obtain spray powder.

[0080] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content was less than 10 ppm), heated to 700° C. at a heating rate of 10° C. / min, and sintered at 700° C. for 8 h.

[0081] After the nitrogen atmosphere box furnace naturally cooled to room temperature, the sintered powder was air flow crushed and then sieved with a sieve to obtain in-situ carbon-coated cobalt-doped LiFe 0.3 Mn 0.696 Co 0.004PO4 material.

[0082] Example 4

[0083] 1.Fe 0.6 Mn 0.398 Co 0.002 -Synthesis of MOF

[0084] First, under a nitrogen atmosphere, 0.995 mol of manganese chloride tetrahydrate, 1.5 mol of ferric chloride hexahydrate and 0.005 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0085] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 202.5 g of 1,4-phthalic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 750 rpm for 30 min at 120°C to prepare the bottom liquid in the reactor.

[0086] Furthermore, the iron and manganese mixed salt solution A prepared above was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 120° C. for 24 hours to obtain a mixed slurry B.

[0087] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.6 Mn 0.398 Co 0.002 -MOF precursors.

[0088] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0089] Lithium carbonate is used as lithium source, ammonium phosphate is used as phosphorus source, Fe 0.6 Mn 0.398 Co 0.002 -MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.6 Mn 0.398 Co 0.002 -MOF precursor was mixed with ethanol and ultrapure water (V:V=1:1) to prepare a slurry with a solid content of 33%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50When the particle size is less than or equal to 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 210°C and an outlet temperature of 100°C. The feed amount is adjusted according to the particle size and outlet temperature to obtain spray powder.

[0090] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content was less than 10 ppm), heated to 750° C. at a heating rate of 5° C. / min, and sintered at 750° C. for 12 h.

[0091] After the nitrogen atmosphere box furnace naturally cooled to room temperature, the sintered powder was air flow crushed and then sieved with a sieve to obtain in-situ carbon-coated cobalt-doped LiFe 0.6 Mn 0.398 Co 0.002 PO4 material.

[0092] Example 5

[0093] 1.Fe 0.4 Mn 0.598 Co 0.002 -Synthesis of MOF

[0094] First, under a nitrogen atmosphere, 1.495 mol of manganese chloride tetrahydrate, 1 mol of ferric chloride hexahydrate and 0.005 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0095] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 170.8 g of 1,3,5-benzenetricarboxylic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 700 rpm for 30 min at 80°C to prepare the bottom liquid in the reactor.

[0096] Furthermore, the prepared iron, manganese and cobalt mixed salt solution A was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 80° C. for 20 hours to obtain a mixed slurry B.

[0097] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.4 Mn 0.598 Co 0.002 -MOF precursors.

[0098] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0099] Lithium carbonate is used as lithium source, diammonium hydrogen phosphate is used as phosphorus source, Fe 0.4 Mn 0.598 Co 0.002 -MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.4 Mn 0.598 Co 0.002 -MOF precursor was mixed with ethanol and ultrapure water (V:V=1:1) to prepare a slurry with a solid content of 35%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50 When the particle size is less than 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 240°C and an outlet temperature of 100°C. 50 ≤25μm) and the outlet air temperature to adjust the feed amount and obtain spray powder.

[0100] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content was less than 10 ppm), heated to 680° C. at a heating rate of 10° C. / min, and sintered at 680° C. for 15 h.

[0101] After the nitrogen atmosphere box furnace naturally cooled to room temperature, the sintered powder was air flow crushed and then sieved with a sieve to obtain in-situ carbon-coated cobalt-doped LiFe 0.4 Mn 0.598 Co 0.002 PO4 material.

[0102] Comparative Example 1

[0103] 1. Synthesis of Carbon-Coated Cobalt-Doped Lithium Manganese Iron Phosphate Composites

[0104] In Comparative Example 1, no Fe synthesis is required. 0.4 Mn 0.598 Co 0.002 -MOF, directly using lithium carbonate as a lithium source, ammonium dihydrogen phosphate as a phosphorus source, manganese chloride tetrahydrate as a manganese source, ferric chloride hexahydrate as an iron source and glucose as a carbon source, and cobalt dichloride as a dopant, lithium carbonate, ammonium dihydrogen phosphate, manganese chloride tetrahydrate, ferric chloride hexahydrate, cobalt dichloride are weighed and mixed with ethanol and ultrapure water (V:V=1:1) according to the same stoichiometric ratio as in Example 1, and glucose with the same mass as the organic ligand in Example 1 is added to the mixed slurry, and the grinding, spraying, sintering, crushing and sieving processes are carried out under the same parameters as in Example 1 to obtain carbon-coated cobalt-doped LiFe 0.4 Mn 0.598 Co 0.002 PO4 material.

[0105] Comparative Example 2

[0106] 1. Synthesis of Carbon-Coated Cobalt-Doped Lithium Manganese Iron Phosphate Composites

[0107] In Comparative Example 2, no Fe synthesis is required. 0.5 Mn 0.496 Co 0.004 -MOF, directly using lithium carbonate as a lithium source, ammonium dihydrogen phosphate as a phosphorus source, manganese chloride tetrahydrate as a manganese source, ferric chloride hexahydrate as an iron source and glucose as a carbon source, and cobalt dichloride as a dopant, lithium carbonate, ammonium dihydrogen phosphate, manganese chloride tetrahydrate, ferric chloride hexahydrate, cobalt dichloride are weighed and mixed with ethanol and ultrapure water (V:V=1:1) according to the same stoichiometric ratio as in Example 2, and glucose with the same mass as the organic ligand in Example 2 is added to the mixed slurry, and the grinding, spraying, sintering, crushing and sieving processes are carried out under the same parameters as in Example 2 to obtain carbon-coated LiFe 0.5 Mn 0.496 Co 0.004 PO4 material.

[0108] Comparative Example 3

[0109] 1. Synthesis of carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0110] In Comparative Example 3, no Fe synthesis is required. 0.3 Mn 0.696 Co 0.004 -MOF, directly using lithium carbonate as a lithium source, ammonium dihydrogen phosphate as a phosphorus source, manganese chloride tetrahydrate as a manganese source, ferric chloride hexahydrate as an iron source and glucose as a carbon source, and cobalt dichloride as a dopant, lithium carbonate, ammonium dihydrogen phosphate, manganese chloride tetrahydrate, ferric chloride hexahydrate, cobalt dichloride are weighed and mixed with ethanol and ultrapure water (V:V=1:1) according to the same stoichiometric ratio as in Example 3, and glucose with the same mass as the organic ligand in Example 3 is added to the mixed slurry, and the grinding, spraying, sintering, crushing and screening processes are carried out under the same parameters as in Example 3 to obtain carbon-coated LiFe 0.3 Mn 0.696 Co 0.004 PO4 material.

[0111] Comparative Example 4

[0112] 1. Synthesis of Carbon-Coated Cobalt-Doped Lithium Manganese Iron Phosphate Composites

[0113] In Comparative Example 4, no Fe synthesis is required. 0.6 Mn 0.398 Co 0.002-MOF, directly using lithium carbonate as a lithium source, ammonium phosphate as a phosphorus source, manganese chloride tetrahydrate as a manganese source, ferric chloride hexahydrate as an iron source and glucose as a carbon source, and cobalt dichloride as a dopant, lithium carbonate, ammonium phosphate dihydrogen, manganese chloride tetrahydrate, ferric chloride hexahydrate, cobalt dichloride are weighed and mixed with ethanol and ultrapure water (V:V=1:1) according to the same stoichiometric ratio as in Example 4, and glucose with the same mass as the organic ligand in Example 4 is added to the mixed slurry, and the grinding, spraying, sintering, crushing and sieving processes are carried out under the same parameters as in Example 4 to obtain carbon-coated LiFe 0.6 Mn 0.398 Co 0.002 PO4 material.

[0114] Comparative Example 5

[0115] 1.Fe 0.4 Mn 0.5 Co 0.1 -Synthesis of MOF

[0116] First, under a nitrogen protective atmosphere, 1.25 mol of manganese chloride tetrahydrate, 1 mol of ferric chloride hexahydrate and 0.25 mol of cobalt dichloride were added to 15 L of dimethyldiformamide and 15 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare a mixed salt solution A of iron, manganese and cobalt.

[0117] Secondly, 15 L of dimethyldiformamide and 15 L of ultrapure water were added to a high-efficiency sealed synthesis reactor, 202.5 g of 1,4-phthalic acid was slowly added to the reactor, and nitrogen protective gas was introduced, and the reaction mixture was stirred at 700 rpm for 30 min at 110° C. to prepare the bottom liquid in the reactor.

[0118] Furthermore, the prepared iron, manganese and cobalt mixed salt solution A was slowly pumped into the reactor using a peristaltic pump. After the mixed salt solution was completely pumped into the reactor, it was stirred for 10 minutes and reacted at 110° C. for 20 hours to obtain a mixed slurry B.

[0119] Finally, after the reactor was cooled to room temperature, the mixed slurry B was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide and ultrapure water (V:V = 1:1) to obtain Fe 0.4 Mn 0.5 Co 0.1 -MOF precursors.

[0120] 2. Synthesis of in-situ carbon-coated cobalt-doped lithium manganese iron phosphate composites

[0121] Lithium carbonate is used as lithium source, ammonium dihydrogen phosphate is used as phosphorus source, Fe 0.4 Mn 0.5 Co 0.1-MOF precursors are manganese and iron sources. Lithium carbonate, ammonium dihydrogen phosphate, Fe 0.4 Mn 0.5 Co 0.1 -MOF precursor was mixed with ethanol and ultrapure water (V:V=1:1) to prepare a slurry with a solid content of 35%, and the mixed slurry was fully ground in a sand mill using 0.2-0.3 mm zirconium balls. 50 When the particle size is less than 0.2 μm, the slurry is transferred to the spray drying process. The spray drying system is set with an inlet temperature of 240°C and an outlet temperature of 100°C. 50 ≤25μm) and the outlet air temperature to adjust the feed amount and obtain spray powder.

[0122] Subsequently, the spray powder was loaded into a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content was less than 10 ppm), heated to 700° C. at a heating rate of 3° C. / min, and sintered at 700° C. for 10 h.

[0123] After the nitrogen atmosphere box furnace naturally cooled to room temperature, the sintered powder was air flow crushed and then sieved with a sieve to obtain in-situ carbon-coated cobalt-doped LiFe 0.4 Mn 0.5 Co 0.1 PO4 material.

[0124] Performance Testing

[0125] Particle size test: The particle size of the lithium manganese iron phosphate composite material obtained in the embodiment and the comparative example was tested using a Malvern laser particle size analyzer. The results are shown in Table 1.

[0126] Powder resistance test: The powder resistance of the lithium manganese iron phosphate composite materials obtained in the embodiment and the comparative example was tested by a ST2742B powder resistivity tester. The measured results are shown in Table 1.

[0127] Electrochemical performance test: The lithium iron manganese phosphate composite material provided in the above-mentioned embodiment and comparative example is mixed with polyvinylidene fluoride and acetylene black in a mass ratio of 92:4:4, and N-methylpyrrolidone is added at a solid content of 30% to perform homogenization, and then coated, dried, and rolled to obtain a positive electrode sheet; a polypropylene film is used as a diaphragm, a lithium sheet is used as a negative electrode, and 1 mol / L LiPF6 (DEC:EC=1:1Vol%) is used as an electrolyte. The positive electrode, diaphragm and negative electrode are assembled in sequence to obtain a lithium-ion battery. The lithium-ion battery was subjected to an electrochemical performance test, and the test conditions were as follows: charge and discharge tests were performed at room temperature of 25°C at rates of 0.1C and 1C, respectively. The results are shown in Table 1. The in-situ carbon-coated cobalt-doped lithium iron manganese phosphate prepared in Example 1 and Comparative Example 1 was subjected to a 0.1C charge and discharge test. The results are shown in Table 1. Figure 1 As shown by Figure 1 It can be obtained that the first discharge specific capacity of Example 1 at a current density of 0.1C is 152.4 mAh / g, and the first discharge efficiency is 96.9%, which is better than the positive electrode material prepared in Comparative Example 1 (the first discharge specific capacity is 135.6 mAh / g, and the first discharge efficiency is 91.9%).

[0128] Compaction density test: The lithium manganese iron phosphate powder samples prepared in the embodiment and the comparative example were compacted by applying a pressure of 5T using a powder compaction density meter, and their volume and mass were measured to calculate the compaction density. The results are shown in Table 1.

[0129] Manganese dissolution test: The inductively coupled plasma test method was used to detect the dissolution amount of Mn in the electrolyte of the battery assembled with the lithium manganese iron phosphate material obtained in the comparative example after cycling 100 times at a current density of 1C. The results are shown in Table 1.

[0130] The in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared in Example 1 was characterized using a scanning electron microscope, and the results obtained are as follows: Figure 2 The test results show that the use of Fe 0.4 Mn 0.598 Co 0.002 -The cobalt-doped lithium manganese iron phosphate synthesized with MOF as the precursor is in the form of uniform nanoparticles after the crushing process, which effectively shortens the lithium ion migration path and increases the lithium ion migration rate.

[0131] Table 1

[0132]

[0133] According to the compaction density test results in Table 1, the compaction density of the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared by the present invention is relatively high, reaching 2.4 g / cm 3 This can be attributed to Fe x Mn 1-x-yCo y -MOF (0<x<1, 0<y<0.01) can in situ generate a highly conductive carbon coating layer densely wrapped on the surface of lithium manganese iron phosphate particles during the sintering process, effectively optimizing the stacking mode of nanoparticles and thereby increasing the compaction density of the material.

[0134] According to the powder resistance test results in Table 1, it can be seen that the powder resistance of Example 1 is significantly reduced compared with that of Comparative Example 1, indicating that the conductivity of the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared by the present invention is significantly increased. This is because the present invention forms a uniform Co element doping in situ on the lithium manganese iron phosphate material, and Co replaces Fe or Mn in the lithium manganese iron phosphate lattice to form a cobalt-doped lithium manganese iron phosphate solid solution phase, which can effectively improve the conductivity of the material. Co catalyzes the organic ligands to form carbon nanotubes during the sintering process and the formation of an in-situ carbon layer of MOF during the sintering process, which can further improve the conductivity of the material and is beneficial to improving the rate performance of the battery.

[0135] From Comparative Examples 1 to 4, it can be seen that the compaction density and conductivity of the carbon-coated cobalt-doped lithium manganese iron phosphate prepared by conventional methods are low, and the rate performance and cycle stability of the lithium-ion battery are poor. This can be attributed to the fact that the manganese, iron and cobalt elements in the lithium manganese iron phosphate prepared by conventional lithium source, phosphorus source, manganese source, iron source and cobalt dopant by mixing and grinding fail to achieve a state of uniform distribution at the atomic level in the material, thereby failing to effectively improve the structural stability and electrochemical performance of the material.

[0136] It can be seen from Comparative Example 5 that the electrochemical performance of the composite lithium manganese iron phosphate prepared by the metal-organic framework precursor doped with excessive Co is poor. This is because the excessive Co doping causes the formation of non-electrochemically active phases or cobalt-containing phosphate solid solution phases in the lithium manganese iron phosphate positive electrode material, which affects the actual capacity and thus reduces the electrochemical performance of the composite material.

[0137] In Table 1, compared with Example 1 and Comparative Example 1, compared with Example 2 and Comparative Example 2, and compared with Example 3 and Comparative Example 3, it can be seen that the amount of manganese dissolution in the embodiments of the present invention is significantly reduced. This is because the occupier doping of the Co element in the lithium manganese iron phosphate lattice and the in-situ coating of the carbon layer can inhibit the Jahn-Teller effect and manganese dissolution, thereby inhibiting the structural collapse of the material during the charge and discharge process and optimizing the cycle stability and rate performance of the lithium manganese iron phosphate.

[0138] The in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared by the present invention has significantly improved conductivity compared with ordinary carbon-coated cobalt-doped lithium manganese iron phosphate. When applied to lithium-ion batteries, it can effectively inhibit the dissolution of manganese during the charge and discharge process, thereby improving the rate performance and cycle stability of the lithium-ion battery.

[0139] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing in-situ carbon-coated cobalt-doped lithium manganese iron phosphate, characterized in that: The following steps are involved: S1. In an inert atmosphere, dissolving an iron source, a manganese source and a cobalt source in a solvent to obtain a solution A; S2. In an inert atmosphere, the organic ligand forming the metal-organic framework is mixed with the solvent to obtain a solution B; S3. adding solution A to solution B, stirring evenly, reacting in an inert atmosphere to obtain a mixed slurry, and then performing solid-liquid separation and washing to obtain a metal-organic framework precursor; S4. The metal-organic framework precursor obtained in step S3 is mixed with a lithium source and a phosphorus source, subjected to grinding treatment, spray drying, and calcined under an inert atmosphere to obtain in-situ carbon-coated cobalt-doped lithium manganese iron phosphate; The general formula of the metal-organic framework precursor is Fe x Mn 1-x-y Co y -MOF, wherein 0<x<1, 0<y<0.

01.

2. The preparation method according to claim 1, characterized in that: The general formula of the metal-organic framework precursor is Fe x Mn 1-x-y Co y -MOF, wherein 0<x<1, 0.001<y<0.

006.

3. The preparation method according to claim 1, characterized in that: In the step S4, the molar ratio of the lithium source, the phosphorus source and the metal source of the metal-organic framework precursor is Li:P:(Fe+Mn+Co)=0.95-1.15:0.95-1.15:

1.

4. The preparation method according to claim 1, characterized in that: The calcination treatment in step S4 is to heat to 500-900° C. at a heating rate of 0.5-20° C. / min for heat preservation sintering.

5. The preparation method according to claim 1, characterized in that: The reaction temperature in step S3 is 80-120°C.

6. The preparation method according to claim 1, characterized in that: The reaction time in step S3 is 5 to 30 hours.

7. The in-situ carbon-coated cobalt-doped lithium manganese iron phosphate prepared as claimed in any one of claims 1 to 6.

8. The in-situ carbon-coated cobalt-doped lithium manganese iron phosphate according to claim 7, characterized in that: The compaction density of the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate is ≥2.4 g / cm 3 , powder resistance <14Ω·cm.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the in-situ carbon-coated cobalt-doped lithium manganese iron phosphate as described in claim 7 or 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method for synthesizing doped lithium manganese phosphate / carbon composite material based on mixed metal organic framework

    CN112952058A

  • Low-temperature lamellar Ni-doped lithium iron phosphate material and preparation method thereof

    CN116093295A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN117199350A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN118419887A

  • Multi-position co-doped lithium iron manganese phosphate composite material, preparation method therefor and secondary battery

    WO2024114174A1

Cited By

  • Composite carbon-coated phosphate material and application thereof

    CN120288735A